Chronotropic Incompetence: What Is a Modifiable Risk Factor? - Vitriyaturrida Vitriyaturrida (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Introduction: The heart rate will increase according to the load given which indicates the ....